EFFECTS OF CIHUAPAHTLI ON UTERINE MOTITITY - POZO, EFREN C DEL; PARDO, E; DERBEZ, J (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1945)
A critical review of the literature on the monocytes of the blood in leprosy
BOL INST ESTUD MED BIOL
Keywords: EFFECTS, CIHUAPAHTLI, UTERINE, MOTITITY; CIENCIAS MEDICAS; FARMACOLOGIA